The quickening : entering into the firestorm of God's grace - [Otis, George]; [Sentinel Group]; [Transform Nations Media] ([United States : [Transforn Nations Media], 2003)
Part inspiration, part instruction, this DVD provides the tools to transform communities.
"DSG2168."
Keywords: Spiritual warfare; Evangelistic work; Intercessory prayer